Relation of Transthoracic Echocardiographic Aortic Regurgitation to Pressure Half-time and All-Cause Mortality - Strom, Jordan B. (Am J Cardiol, 2020)
To evaluate the relation of aortic regurgitation (AR) pressure half-time (PHT) on transthoracic echocardiography (TTE) and all-cause mortality, we screened 118,647 baseline TTE reports from 2000–2017, to identify patients with any AR and PHT data. Patients with infective endocarditis or prior aortic valve replacement were excluded. The relationship of baseline PHT on time to all-cause mortality was evaluated using Cox regression. A total of 2,653 individuals were included (73.1 ± 14.3 years; 53.8% female; PHT, 530 ± 162 ms). Individuals with shorter PHTs more frequently had 3–4+ AR (PHT ≤ 200 ms vs. > 500 ms, 17.9% vs. 0.6%, p < 0.0001). Diastolic parameters (E/e’, E/A ratio, mitral valve deceleration time, pulmonary artery systolic pressure) all significantly correlated with PHT (all p < 0.05). Over a median (IQR) follow-up of 8 (4–11 years), there were 799 (30.1%) deaths at a median (IQR) of 1.9 (0.4–4.3) years. On a univariate basis, a PHT ≤ 320 ms or > 750 ms was significantly related to increased mortality, even amongst those with nonsevere AR. After multivariable adjustment (in particular for E/e’), PHT was no longer significantly related to death. In conclusion, in this large, single center, retrospective study, AR PHT was not independently related to mortality. While a PHT ≤ 320 ms was associated with increased mortality in individuals without severe AR, this relationship was no longer significant after adjusting for diastolic functional variables. Thus, a PHT ≤ 320 ms in individuals without significant AR may indicate prognostically-relevant diastolic dysfunction.